2019
DOI: 10.1097/j.pain.0000000000001509
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic prescribing trends in a national sample of older veterans with osteoarthritis: 2012-2017

Abstract: Few investigations examine patterns of opioid and nonopioid analgesic prescribing and concurrent pain intensity ratings before and after institution of safer prescribing programs such as the October 2013 Veterans Health Administration system-wide Opioid Safety Initiative (OSI) implementation. We conducted a quasi-experimental pre–post observational study of all older U.S. veterans (≥50 years old) with osteoarthritis of the knee or hip. All associated outpatient analgesic prescriptions and outpatient pain inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…While use of analgesics to address pain is common among patients with knee or hip OA, [5][6][7] guideline recommended first-line treatments 2 3 such as exercise therapy and patient education is greatly under-prescribed, 4 despite being associated with at least similar pain relief as the most commonly used analgesics. 2 27 28 Our observational results suggest that exercise therapy and patient education may not only provide pain relief, but may reduce analgesic use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While use of analgesics to address pain is common among patients with knee or hip OA, [5][6][7] guideline recommended first-line treatments 2 3 such as exercise therapy and patient education is greatly under-prescribed, 4 despite being associated with at least similar pain relief as the most commonly used analgesics. 2 27 28 Our observational results suggest that exercise therapy and patient education may not only provide pain relief, but may reduce analgesic use.…”
Section: Discussionmentioning
confidence: 99%
“…4 Instead, analgesics such as paracetamol (acetaminophen) and non-steroidal anti-inflammatory drugs (NSAIDs) are commonly used to address pain associated with knee or hip OA. [5][6][7] A large proportion of patients are also prescribed opioids for their knee and hip OA pain. [8][9][10] Exercise therapy appears to have similar effect sizes to reduce OA pain as the small to moderate effect size of paracetamol and NSAIDs, 2 and a recent study suggested that opioids are not superior to NSAIDs in reducing low back pain and knee and hip OA pain.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Trentalange et al 88 used an interrupted time-series, segmented regression model applied to data from the US national Veterans Health Administration in patients aged 50 years and over with a recorded diagnosis of hip or knee OA. Aggregated monthly prescription rate data were available 22 months before and 38 months after the introduction of the national system-wide Opioid Safety Initiative (OSI) in October 2013.…”
Section: When Less Is More? Deprescribing and Decommissioningmentioning
confidence: 99%
“… 1 , 2 With pain as the predominant symptom of OA, 3 - 5 a growing emphasis of research and clinical practices is being put on pain management. Despite existing drugs such as acetaminophen, opioids, and non-steroidal anti-inflammatory drugs (NSAIDs) being widely used, 6 - 8 to date, there is no analgesic present for OA pain alleviation proven both safe and robustly effective, and the associated adverse effects (AEs) were reported to affect a spectrum of body systems. 9 - 11 Thus, a stringent need for new pain-relieving drugs for OA warrants further investigation in this field.…”
Section: Introductionmentioning
confidence: 99%